Resistance exercise and inflammation in breast cancer patients undergoing adjuvant radiation therapy: mediation analysis from a randomized, controlled intervention trial - Schmidt, Martina; Meynköhn, Anna Lucca; Habermann, Nina; Wiskemann, Joachim; Oelmann-Avendano, Jan Tobias; Hof, Holger; Wessels, Sabine; Klassen, Oliver; Debus, Jürgen; Potthoff, Karin; Steindorf, Karen; Ulrich, Cornelia (International journal of radiation oncology, biology, physics, 2016)
To explore the mediating role of inflammatory parameters in the development of fatigue, pain, and potentially related depressive symptoms during radiation therapy for breast cancer and its mitigation by resistance exercise.